PRIORITAS PENGEMBANGAN BUDIDAYA RUMPUT LAUT KAPPAPHYCUS ALVAREZII DI KAWASAN KLASTER KOLONO KABUPATEN KONAWE SELATAN - Oce Astuti; Emiyarti Emiyarti; Arman Pariakan (Samakia : Jurnal Ilmu Perikanan, 2018)
Cluster Kolono Konawe South, Southeast Sulawesi Province is an area that has the potential of the sea to be developed by seaweed cultivation activities Kappahycus alvarezii, with the benefit of creating regional economic improvement. So far, the development of commercial seaweed cultivation is still lacking so that people's income and local revenue are not optimal. One of the causes is the absence of strategic planning and policy in the development of seaweed cultivation. As a first step, it is necessary to determine the priorities for the development of cultivation K. alvarezii in the Kolono cluster area. The method applied in collecting research data is observation, interviews, and questionnaires. Policy priority scale analysis is determined by the Analytical Hierarchy Process (PHA). The results of the study showed that the cultivation activities of K. alvarezii in the Kolono cluster area, South Konawe District required improvements in several factors, namely the availability of human resources, improvement of the capital system, and the detection of an appropriate aquatic environment. To maintain/sustain the aquaculture business K. alvarezii, some strategic policies are needed. The practical alternative policy that can be done in the short term by the South Konawe District government in the Klater Kolono area is to conduct training and demonstration of cultivation K. alvarezii which includes cultivation design, site selection, planter preparation, seed preparation, maintenance, harvest and post-harvest techniques, processes sales and profit value and capital flow.